CHLORHEXIDINE ALCOHOL VERSUS POVIDONE-IODINE FOR SURGICAL SITE ASEPSIS: A RANDOMIZED TRIAL TO COMPARE OUTCOME IN SURGICAL PATIENTS - Atreya, Anshu; Kumari, Bhawana; Srikant; Kumar, Akhilesh; Kumar, Ashish (Student’s Journal of Health Research Africa, 2024)
Background Common postoperative consequences that raise healthcare expenditures, lengthen hospital stays, and increase morbidity are surgical site infections (SSIs). Chlorhexidine alcohol (CA) and povidone-iodine (PI) are common antiseptics used for preoperative antiseptic skin preparation, which is essential for reducing the risk of superficial skin infections. The study evaluated surgical patients prepped with chlorhexidine alcohol vs. povidone-iodine in terms of the incidence of SSIs. Methods Two groups of 122 individuals each—Category A receiving CA and Category B receiving PI—were randomly assigned to a total of 244 individuals. Patients aged 18-60 undergoing elective non-laparoscopic surgeries were included. Data on demographic details, nutritional status, preoperative random blood sugar, procedure performed, operating time, duration of hospital stay, and secondary wound management interventions were collected. Statistical analysis was done using SPSS version 21.0. Results Both groups were demographically similar. Category A had 5 superficial and 3 deep SSIs, while Category B had 9 superficial and 6 deep SSIs, including a mesh infection after inguinal hernioplasty. Category A had 57 males, 65 females, and a mean age of 40.03 ± 16.09 years; Category B had 63 males, 59 females, and a mean age of 37.92 ± 12.73 years. The mean hospital stay for uncomplicated cases was similar (Category A: 8.84 ± 2.12 days, Category B: 9.0 ± 1.8 days), but patients with SSIs in Category B had longer stays (Category A: 15.21 ± 3.33 days, Category B: 18.23 ± 2.11 days). Conclusion While both antiseptics were effective in general use, CA was associated with a lower incidence of SSIs and shorter hospital stays for infected cases compared to PI. Recommendations For preoperative skin preparation, chlorhexidine alcohol ought to be chosen to lower the risk of SSIs and enhance patient outcomes.